Sodium Benzoate: A D-Amino Acid Oxidase Inhibitor (Zubilance®) Added to Anti-psychotics for the treatment of schizophrenia Management: An Open-Label Study - Banerjee, Debanjan; Singh, Krishna Kumar (Asian Journal of Medical Research, 2025)
Background: Schizophrenia is treated mainly by antipsychotic medication, although one still has to deal with cognitive deficits and suboptimal quality of life often persists. This study evaluates the efficacy of Zubilance®, a sodium benzoate formulation and D-amino acid oxidase inhibitor-as an add-on treatment with antipsychotics-to improve symptom severity, cognitive function, and quality of life in schizophrenia patients. Subjects and Methods: This was a randomized controlled trial with a study duration of 6 weeks. The study group received Zubilance® (500 mg sodium benzoate) in combination with antipsychotics, while the control group received antipsychotics only. Outcomes included symptom severity evaluated by PANSS and CGI scale, cognitive functioning assessed by the MoCA, and quality of life evaluated using the WHOQOL scale. Results: The study group demonstrated a significant improvement in symptom severity, indicated by lower PANSS and CGI scores compared to the control group (p < 0.05). Cognitive function, assessed via MoCA, improved notably in the Zubilance® group, suggesting cognitive enhancement with the add-on treatment. WHOQOL results showed improved quality of life in the study group, correlating with reduced symptoms and cognitive benefits. Conclusion: Our study shows that addition of Zubilance® (Sodium benzoate) to standard antipsychotic drugs treatment improves the patient outcome with enhanced symptom control, cognitive function and quality of life.